The bombing of Pearl Harbor, 1941 - Tarshis, Lauren; Dawson, Scott, 1967- (New York : Scholastic, 2011)
Missing his life in New York City, Danny's planning to stow away on a ship out of Pearl Harbor, but an attack on the harbor impedes his plans.
007-010.
620
Keywords: Pearl Harbor (Hawaii), Attack on, 1941 -- Juvenile fiction; World War, 1939-1945 -- Pacific Area -- Juvenile fiction; Adventure stories; Historical fiction